Avian Influenza H5N6 Viruses Exhibit Differing Pathogenicities and Transmissibilities in Mammals. Issue 1 (December 2017) - Zhao, Zongzheng; Guo, Zhendong; Zhang, Chunmao; Liu, Lina; Chen, Ligong; Zhang, Cheng; Wang, Zhongyi; Fu, Yingying; Li, Jiaming; Shao, Huabin; Luo, Qingping; Qian, Jun; et al.
Abstract Since 2013, highly pathogenic avian influenza H5N6 viruses have emerged in poultry and caused sporadic infections in humans, increasing global concerns regarding their potential as human pandemic threats. Here, we characterized the receptor-binding specificities, pathogenicities and transmissibilities of three H5N6 viruses isolated from poultry in China. The surface genes hemagglutinin (HA) and neuraminidase (NA) were closely related to the human-originating strain A/Changsha/1/2014 (H5N6). Phylogenetic analyses showed that the HA genes were clustered in the 2.3.4.4 clade, and the NA genes were derived from H6N6 viruses. These H5N6 viruses bound both α-2, 3-linked and α-2, 6-linked sialic acid receptors, but they exhibited different pathogenicities in mice. In addition, one virus was fully infective and transmissible by direct contact in guinea pigs. These results highlight the importance of monitoring the continual adaptation of H5N6 viruses in poultry due to their potential threat to human health.